Grasshopper (Zonocerus variegatus L) Infestation and Root Dry Matter Content of Cassava as Influenced by Planting Date and Cassava Genotypes - Torto, Saffea Joseph (2023)
Dearth of information exists on the effects of planting dates and genotypes on grasshopper (Zonocerus variegatus L.) infestation and dry matter accumulation in the root organ of cassava. An experiment was conducted at the School of Agriculture and Food Sciences Experimental site of Njala University site during 2007/2008 and 2015/2016 cropping seasons. This study assessed the effects of planting date and cassava genotypes on grasshopper infestation and root dry matter accumulation in cassava. The experiment utilized four cassava genotypes (Cocoa, SLICASS 1, SLICASS 4 and SLICASS 6) and three planting dates (June, September and December) laid out in a Randomized Complete Block Design (RCBD) with three replications. Findings showed that the incidence and severity of grasshopper attacks, as well as root dry matter contents were significantly (p<0.05) different between variety and planting dates. The grasshopper severity scores increased from 3 months after planting (MAP) (1.6) to 9 MAP (2.6). Similarly, the incidence increased from 3 MAP (23.0 %) to 9 MAP (29.7 %). The lowest percent incidence of grasshoppers was observed in June (24.8%), followed by September (26.0 %), whilst December recorded the highest (30.7 %). Similar trends were exhibited for severity score for June (1.5), September (2.2) and December (2.5) planting dates. Genotype SLICASS 6 (42.21 %) had the highest root dry matter content, followed by SLICASS 1 (42.17 %), while Cocoa and SLICASS 4 had the lowest of 41.90 %. The protected plots recorded higher root dry matter content (44.0 %) than the unprotected plots (40.9 %). Identification of tolerant cassava variety, protection of cassava field from grasshopper infestation and harvesting cassava in December could be exploited for selection and production of tolerant cassava variety with desired processing traits such as high root dry matter content.